Development of a Stringent Ex Vivo-Burned Porcine Skin Wound Model to Screen Topical Antimicrobial Agents - Ping Chen; Eliza A. Sebastian; S. L. Rajasekhar Karna; Kai P. Leung (Antibiotics)
Background: Due to rising antibiotic-resistant microorganisms, there is a pressing need to screen approved drugs for repurposing and to develop new antibiotics for controlling infections. Current in vitro and ex vivo models have mostly been unsuccessful in establishing in vivo relevance. In this study, we developed a stringent ex vivo-burned porcine skin model with high in vivo relevance to screen topical antimicrobials. Methods: A 3 cm-diameter thermal injury was created on non-sterilized porcine skin using a pressure-monitored and temperature-controlled burn device. Commensals were determined pre- and post-burn. The burn wound was inoculated with a target pathogen, and efficacies of Silvadene, Flammacerium, Sulfamylon, and Mupirocin were determined. The in vivo relevance of this platform was evaluated by comparing the ex vivo treatment effects to available in vivo treatment outcomes (from our laboratory and published reports) against selective burn pathogens. Results: Approximately 1% of the commensals survived the skin burn, and these commensals in the burn wounds affected the treatment outcomes in the ex vivo screening platform. When tested against six pathogens, both Silvadene and Flammacerium treatment exhibited ~1–3 log reduction in viable counts. Sulfamylon and Mupirocin exhibited higher efficacy than both Silvadene and Flammacerium against Pseudomonas and Staphylococcus, respectively. The ex vivo treatment outcomes of Silvadene and Flammacerium against Pseudomonas were highly comparable to the outcomes of the in vivo (rats). Conclusions: The ex vivo model developed in our lab is a stringent and effective platform for antimicrobial activity screening. The outcome obtained from this ex vivo model is highly relevant to in vivo.